FoMO, Loneliness, Emotion Regulation, and Academic Burnout as Predictors of Problematic Smartphone Use (PSU) among Vocational High School Teachers - Novi Hidayat; Ziyadi Ali Ikromi; Putri Ayu Widyautami; Neulis Dewi Julaeha Daswilah; Iksal Maulana (Universitas PGRI Yogyakarta, 2026)
The rapid growth of smartphone use offers many benefits but also raises risks of problematic smartphone use (PSU), which negatively affects psychological well-being, job performance, and social interaction. While prior research has largely focused on adolescents and university students, studies on teachers remain limited. To address this gap, the present study examined the effects of fear of missing out (FoMO), loneliness, emotion regulation, and academic burnout on PSU among vocational high school teachers in Bekasi Regency, Indonesia. Using a quantitative ex-post facto design, data were collected from 132 teachers selected through multistage random sampling. Instruments (SAS-SV, FoMO Scale, UCLA Loneliness Scale, ERQ, Academic Burnout Scale) demonstrated excellent validity and reliability (α = 0.923–0.973). Multiple regression analysis indicated a significant effect (F = 6.491; p < 0.001) with R² = 47%. Findings highlight the importance of digital well-being programs through adaptive emotional regulation, workload management, and healthy technology use. Keywords: academic burnout, emotion regulation, FoMO, problematic smartphone use, vocational high school teachers